2019
DOI: 10.1111/cas.14127
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiles of colorectal carcinoma with liver metastases and newly identified fusion genes

Abstract: Every year, approximately 1.2 million cases of colorectal carcinoma (CRC) are newly diagnosed worldwide. Although metastases to distant organs are often fatal complications of CRC, little information is known as to how such metastatic lesions are formed. To reveal the genetic profiles for CRC metastasis, we conducted whole‐exome RNA sequencing on CRC tumors with liver metastasis (LM) (group A, n = 12) and clinical stage‐matched larger tumors without LM (group B, n = 16). While the somatic mutation profiles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…Just over half of all genomic alterations were detected in both paired primary tumor and metastasis samples in our cohort. However, when only focusing on recurrent driver genes, this proportion increased to a level that was similar to that seen in several small CRLM cohorts (approximately 70%) [ 7 , 8 , 30 , 31 ]. This change in proportion may be because systemic spread of colorectal cancer may occur while the tumor is clinically undetectable [ 31 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Just over half of all genomic alterations were detected in both paired primary tumor and metastasis samples in our cohort. However, when only focusing on recurrent driver genes, this proportion increased to a level that was similar to that seen in several small CRLM cohorts (approximately 70%) [ 7 , 8 , 30 , 31 ]. This change in proportion may be because systemic spread of colorectal cancer may occur while the tumor is clinically undetectable [ 31 ].…”
Section: Discussionsupporting
confidence: 67%
“…A large-scale integrated omics study in a Chinese CRC cohort demonstrated the ability of the phosphoproteome to distinguish metastasis and to predict drug response [6]. In research specifically focusing on CRLM, high similarities were observed between primary tumors and liver metastases (LMs), whereas ubiquitous private mutations in LMs suggested individual tumor heterogeneity and specific genetic biomarkers that were capable of predicting potential therapeutics for treating LMs [7][8][9]. However, these studies either handled primary tumors, LMs and other metastases identically or were restricted to quite small numbers of samples.…”
Section: Introductionmentioning
confidence: 99%
“…It is equally interesting that in KRAS mutant colorectal cancers, simultaneous mutations of RYR2, MUC15, and FAT3 are frequent. On the other hand, mismatch repair deficiency is not associated with KRAS mutation in colorectal cancer [ 34 ]…”
Section: Introductionmentioning
confidence: 99%
“…Previous big data studies concerning CRC liver metastasis had achieved accomplishment in identifying altered transcriptome [29] , lncRNAs [30] , or fusion genes [31] that might be responsible for CRC liver metastasis. In all these studies, evidence that associate immune activities with CRC liver metastasis was scarce.…”
Section: Introductionmentioning
confidence: 99%